Propranolol decreases fear expression by modulating fear memory traces - Santos, Sofia Leal (Biol Psychiatry, 2021)
BACKGROUND: Post-traumatic stress disorder (PTSD) can develop following a traumatic event and results in heightened, inappropriate fear and anxiety. Although approximately 8% of the United States population suffers from PTSD, only two drugs have been approved by the FDA to treat it, both with limited efficacy. Propranolol, a non-selective β-adrenergic antagonist, has shown efficacy in decreasing exaggerated fear, and there has been renewed interest in using it to treat fear disorders. METHODS: Here, we sought to determine the mechanisms by which propranolol attenuates fear by utilizing an activity-dependent tagging system, the ArcCreER(T2) x enhanced yellow fluorescent protein (eYFP) mice. 129S6/SvEv mice were administered a 4-shock contextual fear conditioning (CFC) paradigm followed by immediate or delayed context re-exposures. Saline or propranolol was administered either prior to or following the first context re-exposure. To quantify hippocampal, prefrontal and amygdalar memory traces, ArcCreER(T2) x eYFP mice were administered a delayed context re-exposure with either a saline or propranolol injection prior to context re-exposure. RESULTS: Propranolol decreased fear expression only when administered prior to a delayed context re-exposure. Fear memory traces were affected in the dorsal dentate gyrus and basolateral amygdala following propranolol administration in the ArcCreER(T2) x eYFP mice. Propranolol acutely altered functional connectivity between hippocampal, cortical, and amygdalar regions. CONCLUSIONS: These data indicate that propranolol may decrease fear expression by altering network correlated activity and by weakening the reactivation of the initial traumatic memory trace. This work contributes to the understanding of noradrenergic drugs as therapeutic aids for PTSD patients.